Terpenoids from the roots of Leontopodium longifolium and their inhibitory activity on NO production in RAW264.7 cells. Issue 16 (17th August 2020) - Shen, Tong; Qian, Han; Wang, Yong-Dong; Li, Hai-Bei; Xie, Wei-Dong
Abstract: Phytochemical investigation of the roots of Leontopodium longifolium, led to the isolation of a novel norsesquiterpene, named as longifolactone (1 ), along with three known diterpenes. The structures of these compounds were elucidated by analysis of HR-ESI-MS, UV, IR and 1D and 2D NMR spectroscopic data. The absolute configuration of the new compound was determined by electronic circular dichroism (ECD) using both experimental and calculated ECD spectra. Furthermore, their anti-inflammatory effects were evaluated in LPS-activated RAW264.7 cells to determine their effects on the release of NO. Longifolactone (1 ) showed weak cytotoxicity towards two human cancer cell lines. GRAPHICAL ABSTRACT: